Application of Participation (Deelneming) in the Crime of Mistreatment of A Child (Case Study of Decision Number 4/PID.SUS-ANAK/2023/PN JKT.SEL) - Mukti, Muhammad Aryo Dwinanda; Mulyadi, Mulyadi (Universitas Islam Sultan Agung, 2024)
This study analyzes the application of participation theory (deelneming) in child assault cases under Indonesian law, focusing on whether participation in such criminal cases aligns with the principles of criminal law in Indonesia. The research uses a descriptive juridical-normative approach, examining statutory regulations (statute approach) and case law (case approach), specifically the Child Protection Law and the consideration of the panel of judges in Decision No. 4/Pid.Sus-Anak/2023/PN Jkt. Sel. The findings show that the application of participation theory in the case involving AGH, a minor who was involved in organizing the meeting that led to the criminal act, aligns with the principles of child criminal responsibility in Indonesian law. Despite not directly committing physical violence, AGH’s role as an organizer and liaison in the planning of the crime fulfills the elements of participation under Article 55 of the Criminal Code, making him accountable for the offense. Additionally, the application of rehabilitative punishment through sentencing in a Juvenile Detention Center (LPKA) is consistent with the objectives of the Indonesian juvenile justice system. AGH is given the opportunity to receive guidance appropriate to his age and psychological development, in line with the principles of reformation and restorative justice emphasized in Article 71 of Law No. 11 of 2012 on the Juvenile Criminal Justice System. The focus on rehabilitation and education, rather than mere punishment, aims to reintegrate the child into society in a positive and productive manner. In conclusion, while AGH was involved in the crime of maltreatment, the legal process has appropriately considered rehabilitation, ensuring that the legal response aligns with the principles of juvenile criminal law in Indonesia.